Efektywność komunikowania się w relacji lekarz-pacjent - Lewandowska, Bianka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article analyzes the role of the intercommunication in somatic diseases therapy. Two aspects are presented here, defined as: indirectly - and directly therapeutic function of medical communication. The psychological and physiological mechanisms, which decide about the realization of these functions have been also indicated. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 182-198